Commissive Acts Use In Conversation Tangled Movie - Ana Kristina; Ambelagin Ambelagin (Universitas Musamus Merauke, 2022)
This research aimed to find out the types of commissive act in Tangled Movie. In this research, the researchers used Kreidler’s theory of speech act. The researchers used qualitative method to analyzed commissive act in this research. The object of this research was commissive act and the subject was Tangled Movie. This research contained utterances from the movie’s conversation dialogue. Every utterance from the movie had different types commissive act. In collecting the data, this research used non-participatory observation method. The researchers found 15 data in the utterances in Tangled Movie that indicates the use of commissive act. Those data consist of five types of commissive illocutionary act. The first type found by the researcher contained three utterances that expressed refusing act. The second type found by the researcher contained four utterances that expressed promising act. The third type found by the researcher contained four utterances that expressed offering act. Next, the fourth type found by the researchers contained three utterances that expressed vowing act. The last type that found by the researchers contained one utterance that expressed threatening act. The most type that found from the utterance was promising and offering act.